2011
DOI: 10.1007/s00040-011-0196-4
|View full text |Cite
|
Sign up to set email alerts
|

Colony genetic structure in the Australian jumper ant Myrmecia pilosula

Abstract: Eusocial insects vary significantly in colony queen number and mating frequency, resulting in a wide range of social structures. Detailed studies of colony genetic structure are essential to elucidate how various factors affect the relatedness and the sociogenetic organization of colonies. In this study, we investigated the colony structure of the Australian jumper ant Myrmecia pilosula using polymorphic microsatellite markers. Nestmate queens within polygynous colonies, and queens and their mates, were genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Arlequin v3.5 (Excoffier & Lischer 2010) was used to calculate an exact probability test for deviations from linkage equilibrium (LE) and Hardy-Weinberg equilibrium (HWE) using the Markov chain method with default parameters. To decrease the effect of relatedness of individuals, two subsets consisting of either four or one randomly chosen worker(s) per nest were used for these tests (Qian et al 2012). Arlequin was further used to calculate observed (H O ) and expected (H E ) heterozygosities.…”
Section: Methodsmentioning
confidence: 99%
“…Arlequin v3.5 (Excoffier & Lischer 2010) was used to calculate an exact probability test for deviations from linkage equilibrium (LE) and Hardy-Weinberg equilibrium (HWE) using the Markov chain method with default parameters. To decrease the effect of relatedness of individuals, two subsets consisting of either four or one randomly chosen worker(s) per nest were used for these tests (Qian et al 2012). Arlequin was further used to calculate observed (H O ) and expected (H E ) heterozygosities.…”
Section: Methodsmentioning
confidence: 99%
“…Primary polygyny has also been confirmed via microsatellite analysis in two species of the Myrmeciinae: the Australian jumper ant Myrmicia pilosula (Qian et al, 2012) and the red ant Myrmicia rubra (Pearson, 1982(Pearson, , 1983Seppä and Walin, 1996).…”
Section: Ants: Foundress Associations and Primary Polygynymentioning
confidence: 84%
“…d Regression between intranest relatedness and tree sharing index T S (for definition, see "Materials and methods") for each nest. All regressions were fit using a general linear model with a binomial error structure comparing the results in detail, intracolony relatedness was higher in Myrmecia pyriformis (0.51 ± 0.04; Sanetra 2011), lower in Myrmecia brevinoda (0.29 ± 0.01; Qian et al 2011c), and lower in Myrmecia pilosula (0.31 ± 0.01; Qian et al 2011b) than that in M. nigriceps. The first evidence of facultative polygyny in the Myrmecia gulosa group was found by Dietemann et al (2002), who identified two queens in Myrmecia gulosa in two instances.…”
Section: Colony Structurementioning
confidence: 99%